2008
DOI: 10.1007/s11207-008-9267-8
|View full text |Cite
|
Sign up to set email alerts
|

A Quick Method for Estimating the Propagation Direction of Coronal Mass Ejections Using STEREO-COR1 Images

Abstract: We describe here a method to obtain the position of a coronal moving feature in a three-dimensional coordinate system based on height -time measurements applied to STEREO data. By using the height -time diagrams from the two SECCHI-COR1 coronagraphs onboard STEREO, one can easily determine the direction of propagation of a coronal mass ejection (i.e., if the moving plasma is oriented toward or away from the Earth). This method may prove to be a useful tool for space weather forecasting by easily identifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 19 publications
3
92
1
Order By: Relevance
“…The event is connected to a GOES-class B6 flare and partial halo coronal mass ejection (CME) event in active region 10956 on 20 May 2007 (Mierla et al, 2008;Kilpua et al, 2009). Thus, our event is at the lower end of the importance classification of solar eruptions as observed during solar minimum.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The event is connected to a GOES-class B6 flare and partial halo coronal mass ejection (CME) event in active region 10956 on 20 May 2007 (Mierla et al, 2008;Kilpua et al, 2009). Thus, our event is at the lower end of the importance classification of solar eruptions as observed during solar minimum.…”
Section: Introductionmentioning
confidence: 84%
“…The corresponding CME event on 20 May 2007 has been discussed by Mierla et al (2008) using data from Inner Coronagraph (COR1) of the Sun Earth Connection Coronal and Heliospheric Investigation (SECCHI) experiment from two view-points, inferring the CME direction and de-projected velocity. Kilpua et al (2009) showed that this de-projected velocity matches much better the transit time of the MC than the projected velocity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with an assortment of in-situ, radio, and EUV imaging instruments, both STEREO carry two coronagraphs (COR1 and COR2) and two heliospheric imagers (HI-1 and HI-2), aligned such that their fields of view cover the angular (elongation) range from the Sun to 90°. Following the first attempts of triangulation using COR1 and COR2 observations by Mierla et al (2008) and Howard & Tappin (2008), respectively, a large number of 3-D reconstruction techniques using the coronagraphs has emerged in the literature. The earlier reconstruction techniques are reviewed by Mierla et al (2010) but the number of different techniques continues to grow.…”
Section: -D Reconstruction Techniquesmentioning
confidence: 99%
“…The propagation parameters extracted from a single point of view (i.e., one spacecraft) do not give reliable information on the actual CME propagation path. Extraction of the parameters from two vantage points (i.e., both spacecraft), however, makes reconstruction of a true CME propagation path in 3D space possible (Howard & Tappin 2008;Mierla et al 2008Mierla et al , 2010Boursier et al 2009;Colaninno & Vourlidas 2009;de Koning et al 2009; de Koning & Pizzo 2011). The reconstruction can be accomplished using a technique of geometric triangulation, such as that proposed by Liu et al (2010) and Mays et al (2015).…”
Section: Introductionmentioning
confidence: 99%